ANALISIS RESIKO PADA EVALUASI PENAWARAN PENYEDIA JASA PEKERJAAN KONSTRUKSI - Suatan, Mosedayan; Sompie, Bonny F.; Tarore, Huibert (JURNAL ILMIAH MEDIA ENGINEERING, 2012)
Viewed from the owner side, service provider selection process of the construction tender has a considerable impact on overall project costs. Until now the general principles used in the selection of the selection of goods / services are based on technical evaluation and the evaluation of the offer price of everything is based on an evaluation of the knockout, the method is commonly called the lowest bid. The purpose of this study is to determine the factors and sources of any risks that affect the evaluation services offer the construction work at the Department of Transportation, Telecommunications and Informatics of North Sulawesi Province.Object of research conducted at the Department of Transportation, Telecommunications and Informatics of North Sulawesi Province. The process of collecting data by survey techniques, interviews and filling in a questionnaire that further analysis using the Analytical Hierarchy Process (AHP).The results of this analysis is obtained weighting the risk factors and the weight of the sources of risk that need to be considered in bid evaluation process of construction services in the Transport Department of Telecommunications and Informatics of North Sulawesi Province. Knockout method or so-called lowest bit which made the offering price as a major category in this study became the second most important after the categories of financial capability.From this study it can be concluded that the lowest bid price (lowest bid) should not be a major criterion in the evaluation of offers construction services. Suggestions can be submitted which required a change in the concept of the tender evaluation criteria of low-price contracting became a best-value contracting criteria where other criteria along with price and technical form values to consider.Keywords: evaluation, procurement, construction, lowest-bid, best value, AHP